Redefining acute kidney injury - Uma Ali; Nisha Krishnamurthy (Wolters Kluwer Medknow Publications, 2018)
Specific criteria using easily available biomarkers such as serum creatinine and urine output have been developed to define and stage acute kidney injury(AKI) at the bedside. The RIFLE criteria and the AKIN criteria are used for adults, the pRIFLE criteria for children and the KDIGO classification for both adults and children. The chief limitation in all the current criteria lies with the physiological limitations of using an insensitive functional marker such as serum creatinine as a surrogate marker for glomerular filtration rate (GFR). Varying methodologies for measuring serum creatinine and the lack of validation using isotope dilution mass spectrometry(IDMS), are additional technological limitations that challenge uniformity in India. Calculation of eGFR by the Schwartz formula is compromised by these technological limitations as well as by the lack of a validated k value for Indian children. Serum Cystatin C is superior to creatinine as a biomarker for GFR and appears at least 24 hours earlier than serum creatinine in the presence of AKI. However, expense and non- availability in clinical laboratories precludes its use. Urinary biomarkers appear very sensitive and reflect different stages of cell injury. Neutrophil Gelatinase associated Lipocalin (NGAL) has been shown to appear in the urine as early as 2 hours after renal injury. However, it is not specific for AKI alone and may also be increased in many inflammatory states and co-morbid conditions. The redefined criteria for AKI are invaluable in the critical care setup but need further refinement.